Didymin Ameliorates Liver Fibrosis by Alleviating Endoplasmic Reticulum Stress and Glycerophospholipid Metabolism: Based on Transcriptomics and Metabolomics - Li Y; Li C; Xiong Y; Fang B; Lin X; Huang Q (Dove Medical Press, 2022)
Yan Li,1,* Cuiyu Li,1,* Yuhua Xiong,1 Bin Fang,1 Xing Lin,1 Quanfang Huang2 1Life Sciences Institute, Guangxi Medical University, Nanning, Guangxi, 530021, People's Republic of China; 2The Pharmaceutical Department, Guangxi University of Chinese Medicine First Affiliated Hospital, Nanning, Guangxi, 530023, People's Republic of China*These authors contributed equally to this workCorrespondence: Xing Lin, Guangxi Medical University Life Sciences Institute, Nanning, Guangxi, 530021, People's Republic of China, Email gluck4668@sina.com Quanfang Huang, The Pharmaceutical Department, Guangxi University of Chinese Medicine First Affiliated Hospital, Nanning, 530023, People's Republic of China, Email g723m6@sina.comIntroduction: Origanum vulgare L. is a traditional Chinese herb, having a strong hepatoprotective effect. In our previous experiments, we have isolated an ingredient from this herb and identified it as didymin. This study aimed to investigate the effects and underlying mechanisms of didymin on liver injury and fibrosis, elucidating whether it was the pharmacodynamic material basis of Origanum vulgare L.Methods: Mice were injected with CCl4 for 10 weeks to induce liver fibrosis, followed by didymin treatment for 6 weeks. Then, biochemical analysis and histopathological examinations were conducted to evaluate the therapeutic effects of didymin in alleviating fibrosis. Next, the possible mechanisms of didymin were predicted by transcriptomics and then verified by the multiple relevant examinations.Results: The pharmacodynamic experiments indicated that didymin significantly attenuated CCl4-induced hepatic injury and fibrogenesis, as evidenced by the ameliorative pathological tissue, low transaminase activity, and decreased collagen accumulation. Interestingly, the transcriptome analysis predicted that the potential targets were likely to be endoplasmic reticulum stress (ERS), inflammation, apoptosis, and metabolic pathways. And the predictions were then verified by the following examinations: (1) didymin significantly inhibited ERS by regulating the ATF6, IRE1α, and PERK pathways; (2) didymin markedly alleviated hepatocyte apoptosis by restoring the expression of Bcl-2 and caspase families, as well as the mitochondrial dysfunction; (3) didymin significantly decreased the production of the pro-inflammatory cytokines (IL-1β and IL-6); (4) didymin inhibited the glycerophospholipid metabolism pathway by decreasing the synthesis of phosphatidylethanolamines and phosphatidylcholines.Conclusion: Our findings demonstrate that didymin can ameliorate liver fibrosis, which is mainly attributed to the inhibition of ERS, inflammation, and glycerophospholipid metabolism.Keywords: didymin, transcriptomics, metabolomics, liver fibrosis, endoplasmic reticulum stress, ERS